(untitled) (Journal of Mathematics Mechanics and Computer Science, 2018)
Attitude determination and control system is one of the main subsystems of the satellite which provides its orientation in a predetermined direction during the flight. Mathematical models and algorithms providing the required quality of control processes of satellite rotational motion that are used in attitude determination and control system are one of its important elements. This article discusses the problem of satellite attitude determination and control system transient processes quality providing. Quality of transient process is characterized by parameters such as transient process time and oscillation. The required quality of transitional process is reached by tuning of control laws parameters that can be performed with the help of different methods. In this article tuning of control law parameters is implemented with poles placement method. Wherein, to set the location of the roots of characteristic equation of closed-loop control system in the complex half-plane the common practice distributions were used. According to the results of numerical modeling of rotational motion of the satellite under control with calculated parameters of the law it was determined the distribution of roots of characteristic equation providing the required quality of transients processes.